Styling the Sacred: Helwa Bashel and the Construction of a Pop-Islam Typology in Indonesia - Fatimah Laily Rohmah (Journal of Digital Religion and Contemporary Society, 2026)
This study analyzes the practice of modest fashion produced by influencer Helwa Basheel on TikTok through Judith Butler’s framework of gender performativity. Based on netnography of content and comments (2022–2025), this study shows that Helwa constructs a strategic and versatile pastel hybrid pashmina aesthetic that is acceptable across different groups, aesthetically pleasing enough to encourage virality, and commercial enough to attract the Gen Z market. The repetition of gestures, color choices, and subtle religious narratives plays a role in softening the historical dichotomy between the square headscarf (NU–Muhammadiyah) and the long khimar (Salafi), resulting in a new typology that is more fluid, adaptive, and in tune with algorithmic logic. The comments section then functions as a secondary performative arena where Gen Z collectively renegotiates the boundaries of piety, shifting from doctrinal references to aesthetic considerations and purchasing power. These findings indicate a shift in religious authority from clerics to influencers and the emergence of a soft, commercial, and easily imitable form of digital piety.